OUTCOME OF PONSETI METHOD IN TREATING CONGENITAL IDIOPATHIC CLUBFOOT: FIVE YEARS' EXPERIENCE AT A TERTIARY HOSPITAL - Daun, Edewet; Yazid Bajuri, Mohd; Abd Rashid, Abdul Halim; Ibrahim, Sharaf; Das, Srijit (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The earliest non-surgical treatment for the correction of congenital idiopathic talipes equinovarus (CTEV) deformity was described by Ignacio Ponseti. He suggested gentle manipulation and serial applications of casts followed by a period of bracing to maintain the correction. The main objective of this study was to evaluate the result of the Ponseti method with a subjective clinical scoring system using Pirani score, to compare the results with the published literature and to evaluate the effectiveness of foot abduction orthosis (FAO) or ankle-foot orthoses (AFO) in preventing relapse following correction. Methods: A cross-sectional study which was conducted at the Paediatric Orthopaedic Clinic, Universiti Kebangsaan Malaysia Medical Centre (UKMMC). A minimum of 12 months follow-up casting was observed before the patient was subjected to the subjective clinical scoring system. A total of 25 patients which included 5 right feet, 9 left feet, and 10 bilateral feet with idiopathic clubfeet were treated with Ponseti serial casting. Percutaneous Achilles tendon tenotomy was done for 28 feet (82.35%) to correct the equinus to achieve full correction. Results: Our results showed that the Ponseti method for treating CTEV was comparable to other published studies. Satisfactory and good results were observed in 97% of cases. A total of 41.18% underwent re-tenotomy of tendon Achilles due to recurrent and persistent equinus. Conclusion: The treatment of CTEV using Ponseti method will increase the successful correction. Meanwhile, the FAO gave better results for maintenance and prevention of recurrent deformity, compared to the AFO.